Pengenalan Investasi Pasar Modal Bagi Kalangan Mahasiswa dan Pelajar Melalui Seminar Edukasi - Syarif Hidayatullah; Aep Saefullah; Abdul Kohar; Arief Syahreza (I-Com: Indonesian Community Journal, 2024)
The importance of introducing capital market investment to students and students is highlighted in increasing financial understanding and investment interest in youth. One effective approach is through educational seminars that can provide practical knowledge and in-depth understanding. This community service aims to introduce capital market investment to students and students. The activity involved 100 participants consisting of STIE Ganesha students and SMK Nusantara Ciputat students on September 15, 2023 in the Hall room on the second floor of the STIE Ganesha Campus. The activity method uses seminars, socialization, counseling and question and answer. The results of the activity show that educational seminars are effective in increasing knowledge and investment interest among students and students. Participants showed significant improvement in their understanding of the basic concepts of capital markets, existing investment instruments, and risk management. In addition, participants also showed increased interest in starting to invest in the capital market after attending the seminar. The activity has important implications in the development and implementation of educational seminars on capital market investment for students and students. This kind of seminar can be used as an effective means to increase their knowledge, understanding, and interest in investing, thus helping them in taking better financial decisions in the future